Rewriting the script: gene therapy and genome editing for von Willebrand Disease - Barraclough, Alastair; Bär, Isabel; van Duijl, Tirsa; Fijnvandraat, Karin; Eikenboom, Jeroen C. J.; Leebeek, Frank W. G.; Bierings, Ruben; Voorberg, Jan; Trasanidou, Despoina (Frontiers in Genome Editing, 2025)
In recent years gene therapy has emerged as a powerful technology for treatment of a large variety of inherited disorders. With the FDA approval of in vivo gene therapy of hemophilia A and B using AAV-mediated transgene delivery to hepatocytes, the path towards a new treatment era seemed paved. Also, CRISPR-Cas based approaches have reached the clinic, as in the ex vivo treatment of hematopoietic stem cells for sickle cell disease and thalassemia patients. The question arises whether these innovative strategies will also be suitable for patients with von Willebrand Disease (VWD). Whilst in and ex vivo delivery to endothelial cells (ECs) has been demonstrated, and CRISPR-Cas9 gene editing has been successful in ECs, there are currently no gene therapy options available for VWD. The wide variety of pathogenic VWF mutations makes development of broadly applicable, cost-effective gene therapies challenging. While delivery of von Willebrand factor (VWF) as a therapeutic transgene would be optimal, the size of VWF challenges efficient delivery. Therefore, treatment of VWD requires targeted, personalized gene therapy; for instance by using the newest CRISPR-Cas technologies which can be tailored to facilitate alteration and restoration of various pathogenic VWD variants. This review describes the inherited bleeding disorder VWD and potential gene therapy approaches for management of the disease. Thereby we are exploring different CRISPR-Cas technologies and recent developments in the field. Moreover, we will discuss the ongoing advances of in vivo delivery systems, all with the scope on ECs.